Effect of WMA additive on properties of PPA-modified asphalt binders containing anti-stripping agent. Issue 4 (21st March 2021) - Ghabchi, Rouzbeh; Rani, Shivani; Zaman, Musharraf; Ali, Syed Ashik
ABSTRACT: The current study was undertaken to evaluate the effect of Polyphosphoic Acid (PPA) on rheological properties of different grades of asphalt binders containing a chemical Warm-Mix Asphalt (WMA) additive in presence and absence of a liquid Anti-Stripping Agent (ASA). Also, the effect of chemical WMA additive, PPA and ASA on rutting and moisture-induced damage potential of asphalt mixes was evaluated. Polymer-modified and non-modified asphalt binders were blended with different amounts of PPA, WMA additive, and ASA and tested in a Dynamic Shear Rheometer and a Bending Beam Rheometer. The results indicated that blending WMA additive and PPA with all tested binders increased their rutting and fatigue resistance. However, blending PPA with asphalt binders in presence of the WMA additive and ASA was found to reduce their resistance to fatigue cracking. Also, the use of WMA additive, ASA and PPA was found to reduce the effectiveness of the PPA in bumping the high-temperature Performance Grade (PG) of asphalt binder with an insignificant effect on low-temperature PG. Furthermore, conducting Hamburg wheel tracking and indirect tensile strength ratio tests on asphalt mixes containing WMA additive, PPA and ASA  showed a low susceptibility to rutting with no significant indication of moisture-induced damage.